Dynamic Information and Analytical System for Assessing and Managing Acquired Knowledge - Goncharova, Yana (2022)
The paper presents the concept of a system for the intellectual digital e-univer-sity of the future (IDEUF) based on an integrated database that ensures the correct function of the whole university system. Particular attention is paid to the process of checking students’ required and current level of acquired knowledge, which is considered one of the main parts of the educational process. The article provides a detailed comparative analysis of actual testing systems and presents a proper testing system model within the IDEUF framework. The proposed system considers the testing principles, scales, and technologies for test building and preparing educational materials